2023
DOI: 10.1021/acs.energyfuels.3c00569
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Storage Characteristics and Redox Behaviors of Lanthanum Perovskite Oxides with Transition Metals in the B-Sites

Abstract: Perovskites are typical oxygen storage materials that find many chemical, energy, and environmental applications. Lanthanumbased perovskite oxides represent a large family of oxygen carriers for chemical looping processes. Oxygen storage and redox behaviors are crucial for efficient activation of C−H/C�O, selective oxidation/ combustion, heat management for chemical looping, or lattice oxygenrelated reactions. The present work studied oxygen releasing/acquiring behaviors of lanthanum-based perovskite oxides wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 70 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Perovskite-type mixed oxides (ABO 3 ) are widely used in industry due to their low price, high stability, and good optical, magnetic, electronic, and ferroelectric properties [14]. Additionally, perovskites present interesting catalytic properties that mainly depend on the nature of B metal and that can be modulated by adding some transition metals able to improve their redox properties (associated with the oxidation state of B metal and the formation of oxygen vacancies) and, therefore, catalytic activity [15,16]. Recent results have revealed that these catalysts can be used for the control of pollutants generated by ICEs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite-type mixed oxides (ABO 3 ) are widely used in industry due to their low price, high stability, and good optical, magnetic, electronic, and ferroelectric properties [14]. Additionally, perovskites present interesting catalytic properties that mainly depend on the nature of B metal and that can be modulated by adding some transition metals able to improve their redox properties (associated with the oxidation state of B metal and the formation of oxygen vacancies) and, therefore, catalytic activity [15,16]. Recent results have revealed that these catalysts can be used for the control of pollutants generated by ICEs [17,18].…”
Section: Introductionmentioning
confidence: 99%